The effectiveness of calcium silicate in preventing ice-ice disease and production performance of Kappaphycus alvarezii - Wirantari, Ayu Puspa; Nirmala, Kukuh; Supriyono, Eddy; Hamim, Hamim (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
The cultivation of Kappaphycus alvarezii faces serious challenges due to ice-ice disease outbreaks. This disease is caused by fluctuating environmental conditions that induce stress in the seaweed. Ice-ice disease is characterized by thallus whitening, softening, and fragility, which can lead to a reduction in yield and directly impact the economic returns for seaweed farmers. This study aims to evaluate the effectiveness of calcium silicate (CaSiO3) dosing as a mineral source for the prevention of ice-ice disease and the growth of K. alvarezii seaweed. The experimental design used was a completely randomized design with three replications across four treatments: CaSiO3 doses of 0, 1.6, 1.8, and 2 g/L. The study used an initial weight of K. alvarezii of 100 g per tie. The experiment was conducted through a field trial in seawater using an off-bottom cultivation method. The results indicated that the group with the highest dose of CaSiO3 (2 g/L) produced the best ice-ice resistance, with treatment D showing 17.77 ± 5.09% at the population level and 0.25 ± 0.015 at the individual level, which was statistically significant (P<0.05). Optimal CaSiO3 dosing can be a potential cultivation strategy to improve resistance to ice-ice disease and increase the productivity of K. alvarezii. Keywords: ice-ice, Kappaphycus alvarezii, mineral, nutrient enrichment, seaweed ABSTRAK Budidaya rumput laut K. alvarezii menghadapi tantangan serius akibat serangan penyakit ice-ice. Penyakit ini disebabkan karena kondisi lingkungan yang berfluktuatif sehingga menyebabkan rumput laut menjadi stres. Penyakit ice-ice ditandai dengan pemutihan talus, talus menjadi lunak, dan mudah patah. Penyakit ini dapat mengurangi hasil panen yang berdampak langsung pada keuntungan ekonomi bagi pembudidaya rumput laut. Penelitian ini bertujuan untuk mengevaluasi efektivitas pemberian dosis kalsium silikat (CaSiO3) sebagai sumber mineral terhadap pencegahan penyakit ice-ice dan pertumbuhan rumput laut K. alvarezii. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan tiga kali ulangan pada empat perlakuan yaitu dosis CaSiO3 0, 1,6, 1,8, dan 2 g/L. Penelitian ini menggunakan berat awal K. alvarezii sebesar 100 g per ikatan. Pengujian dilakukan dengan percobaan lapangan di perairan laut dengan metode lepas dasar. Hasil penelitian menunjukkan bahwa kelompok dengan dosis CaSiO3 tertinggi (2 g/L) secara signifikan (p<0,05) menghasilkan persentase ice-ice terbaik yaitu pada perlakuan D sebesar 17,77 ± 5,09% pada level populasi dan sebesar 0,25 ± 0,01% pada level individu. Pemberian CaSiO3 pada dosis optimal dapat menjadi strategi budidaya yang potensial untuk meningkatkan ketahanan dari penyakit ice-ice dan produktivitas K. alvarezii. Kata kunci: ice-ice, Kappaphycus alvarezii, mineral, pengayaan nutrisi, rumput laut